(untitled) (Fiep Bulletin - online, 2017)
This article deals with the importance of the implementation and development of a public policy for the healthy aging ofthe population aged 60 or more in the city of Campos dos Goytacazes. Thus the aim of this study is to present the locations ofpractitioners Active Life Program Gymnastics for healthy aging highlighting the importance of physical activity for those who growold. The study methodology was up the location of the elderly (74 ± 5 years), the Active Mangabinha Life program because thisprogram takes place in the city of Campos dos Goytacazes in Tamandaré District. Aiming to contextualize the proposed activitiesas a program consisting of systematic classes three (3) times a week with 60-minute sessions, with each session consisted of 40minutes of body movement exercises with own body weight. Healthy Aging Program, located in Tamandaré district, which has14.8% of students frequent systematic classes, since 22% of seniors who participate live in the city center, getting about 2km.Demonstrating that 36.8% of project participants are the neighborhoods or around the distance of the local school. Already thestudents are around 2 to 5 km from the project, making a total of 48.5% of the participants are the following locations; SantoAntônio, Imperial Park, Turf Club, Juliao Nogueira, Aurora Park, Park Leopoldina, Sao Caetano Park, Finazinha Park, Chestnut,Rio Garden and Park Road. It concludes that more than 60% of the students are from other distant areas of the headquarters ofthe Active Life, which is in Tamandare Park. And the absence of a municipalist public policy toward the health of the agingpopulation, less than 1% of the elderly are tended in their basic needs, moving in search of their participation in the activities.